Sintesis Zn-BDC dengan Metode Sonokimia dan Aplikasinya Pada Proses Adsorpsi Ion Logam Pb2+ - Fauzi Abdilah; Mentik Hulupi; Keryanti Keryanti; Nida Nabilah; Tiana Hasna Nabilah (REACTOR: Journal of Research on Chemistry and Engineering, 2022)
The heavy metal ion pollution such as lead (Pb2+) in wastewater is an environmental problem that needs to be solved. The adsorption method has been reported to have good potential as an alternative method for reducing heavy metal contents in aquatic environment. The most widely used adsorbent media are porous materials with a large surface area and low density. Metal Organic Frameworks (MOFs) are a type of porous material that is widely applied in various fields, such as fuel purification, solvent recovery, gas storage, and adsorbents. Lead(II) is a heavy metal ion that can pollute the environment and endanger humans. This study aims to synthesize MOFs and apply it to the Pb2+ adsorption process. In this research, MOFs type Zn-BDC or MOF-5 were synthesized by sonochemistry method at 60 ℃ as adsorbent for Pb2+ ion. Characterization of the adsorbent by FTIR showed the presence of functional groups C=O, C-H, and Zn-O which indicated the formation of the MOF-5 compound. The concentrations of Pb2+ ions were analyzed using Atomic Absorption Spectrophotometer (AAS). The experimental results show the optimum conditions for the adsorption process at pH 5 for 60 minutes with adsorption efficiency reaching 93.41%. Testing the adsorption isotherm model showed that the Pb2+ ion adsorption process using Zn-BDC as an adsorbent followed the Langmuir isotherm model with the R2 value of 0.9986.